ANALISIS EFEKTIVITAS SISTEM DAN PROSEDUR PELAYANAN PADA KANTOR DINAS PENDAPATAN DAERAH KABUPATEN KUTAI TIMUR - Husain, Takdir (PREDIKSI, 2016)
This study aims to determine and describe the effectiveness of the systems and procedures of public services at the Department of Revenue of East Kutai. The approach used in this study is a qualitative descriptive approach. The results showed that the effectiveness of the systems and procedures in the Office of East Kutai Regency Revenue amounted to 83.96% and the results included in the interval 76% - 100% and this means included in either category. In other words, it can be concluded that the implementation of systems and procedures at the Revenue Office of the East Kutai Regency is effective. Means that the hypothesis formulated in this study can be received and verified.